O21.6 A Tale of Two Cities: Treponema Pallidum Macrolide Resistance in Colombo (Sri Lanka) and London (United Kingdom). (13th July 2013) - Mallikarachchi, D; Hodson, L; Duckett, C; Weerasinghe, G; Buddhakorale, K; McClure, M; Taylor, G; Tipple, C
Abstract : Background: The bacterium Treponema pallidum ( T. pallidum ) causes syphilis. Penicillin is effective treatment, but azithromycin (a macrolide) is a single-dose oral alternative for those with allergy. Unfortunately, macrolide resistance secondary to one of two 23S ribosomal RNA (rRNA) point mutations (A2058G and A2059G) is now wide-spread. Molecular strain-typing suggests that epidemics and macrolide resistance are unlikely the spread of single clones. We present typing and macrolide resistance data from two geographically distinct populations: Colombo, Sri Lanka and London, UK. Methods: Cross-sectional studies were conducted at the Colombo District STD clinics and St Mary's Hospital, London. Ulcer exudate and/or blood were collected from patients with microbiologically confirmed syphilis. Presence of T. pallidum DNA ( tpp047 gene) was confirmed with PCR. Next, using published techniques, the 23SrRNA gene was PCR-amplified for a point-mutation assay and tpp0548, arp and tprE, G & J amplicons were used for strain-typing. Results: Sri Lanka: 24 T. pallidum PCR-positive samples were collected. Patients were men (45.9% MSM) and 91.6% Sinhalese with a mean age of 28 (range 29). None were HIV-1 infected. Two strain types were discovered (14b/f and 13b/f), neither harbouring macrolide resistance. London: 43 men were recruited, 18 in 2006–8 and 25 in 2011–12. Mean age was 37.5 (range 43); 95.2% were MSM and 62.8% were HIV-1 infected. Half (22/43) were white British. A total of 5 full and 14 partial strain types were identified, of which 6 were unique. Macrolide resistance increased from 66.7%(12/18) in 2006–8 to 80%(20/25) in 2011–12. Conclusion: Colombo T. pallidum strains have limited diversity with no macrolide resistance. London strains are more varied and increasingly macrolide-resistant. Ethnic diversity in London exceeds Colombo's and may explain increased strain diversity. In contrast to Sri Lanka, azithromycin is widely used to treat Chlamydia and non-specific urethritis in the UK thus selection pressure may be driving macrolide resistance.